Accountability of Village Fund Management with the Village Financial System Application: Akuntabilitas Pengelolaan Dana Desa dengan Aplikasi Sistem Keuangan - Maharani, Nazilah Indu; Widodo, Heri (Indonesian Journal of Law and Economics Review, 2024)
The general background village fund management has become an essential aspect of local governance, ensuring transparency and accountability in rural development. Specific background the use of accounting systems in village fund management is regulated by government policies, including the application of financial system software to streamline reporting and accountability processes. Knowledge gap however, there is limited research that evaluates the effectiveness of these systems at the village level, particularly in terms of their transparency and participatory mechanisms. Aims this research aims to analyze the implementation of the accounting system in village fund management, focusing on its transparency, accountability, and public participation. Results the findings reveal that the village fund management in Ngampelsari Village is conducted transparently, with clear accountability from the planning stage to reporting and evaluation. Novelty this research provides new insights into how the adoption of the Siskeudes application enhances the transparency and accountability of village fund management, which has not been extensively explored in previous studies. Implications the results suggest that the village government should continue updating and refining the system to maintain public trust and ensure effective fund management, while future research should expand the scope to include multiple villages for comparative analysis. Highlights: Transparent accounting improves village fund management efficiency. The Siskeudes application enhances financial reporting accuracy. Public participation is vital for accountable village governance. Keywords: Governance, Management, Transparency, Accountability, Siskeudes